CONTROL SYSTEM OF JOINED FORCES OF LAW ENFORCEMENT FOR LARGE-SCALE ANTI-TERRORIST OPERATION - Miroshnichenko, G.; Shvetsov, A.; Borodin, B. (Honor and Law, 2020)
In modern conditions, the armed struggle against terrorism creates a problematic situation which involves the lack of the unified form of control system of law-enforcement forces of state law enforcing agencies in the conditions of the development of asymmetric armed confrontation. The solution to the problem situation depends on resolving the contradiction between the traditional hierarchical form of management of state law enforcing agencies and the need to create a multi-functional network of a central form of operational management of the interdepartmental group of law-enforcement forces in conducting anti-terror activities. The practice of applying a unified command in the armed conflict in Syria by uniting armed groups the Desert Gerfalcons, the Islamic Revolutionary Corps, units of the 5th Assault Corps of the Syrian Army, Hezbollah and Fatimid units under the single command of General Sukhela points that separate armed units received effective control through synchronization (coordination, interaction and management) during hostilities. Management of interagency grouping in real time requires timely solution of information and operational tasks with the use of communication and informatization systems, which provides for the communication system of law-enforcement forces to unite with the main communication operators of the state and requires a single special management body. Therefore, for the effective command of law-enforcement forces during a special operation (conducting anti-terrorist and combat operations) were defined a single special governing body - Special Operational Command of interdepartmental group, which in the future should be entrusted with responsibility for operational planning and general management of anti-terrorist activities in the conditions of deployment of asymmetric armed confrontation. Deployment of the network system of the Special Operational Command of the interdepartmental group is a set of measures that provide for the preparation and deployment of a system of control points and organization of management, preparation and deployment of communications and information to ensure both centralized and decentralized forces of law-enforcement achievement of the assigned goal at coordination of military and anti-terrorist actions according to the unified concept and the plan of large-scale special operation.